#194 Anti-leucoderma activity of whole plant extract of Cleome chelidonii - V, Kavitha; T, Shri Vijaya Kirubha; R, Senthamarai (Journal of Pharmaceutical Chemistry, 2022)
Skin diseases, especially Leucoderma (or) Vitiligo, is an important widespread disease all over the world. Vitiligo is a skin condition characterized by “White patches resulting from the loss of pigment. Cleome chelidonii Linn. is a traditional plant belonging to the family Capparaceae. It is grown as perennials throughout dry seasons. It has pink rose (or) white color flowers. (Tamil name–Naikakadugu). The leaves of Cleome chelidonii are claimed to have medicinal properties and are generally known to be used to treat colic, dysentery, headache, otitis, and rheumatism. The whole plant has also been found to possess multiple therapeutic properties, such as its use of a vermifuge in treating skin diseases including leucoderma, and with anti-inflammatory, antimicrobial, antinociceptive, antipyretic properties. The present study gives the systematic evaluation of the antileuderma activity of the rare plant Cleome chelidonii. Prior to anti-leucodermal activity, the test extracts of Cleome chelidonii were subjected to a skin irritation test performed in rabbits and were found to be non-irritant in nature. Anti-leucoderma activity for the chloroform, acetone, and methanol extracts of Cleome chelidonii were studied in 6J BL C57 Black mice model by the induction of depigmentation by applying 5% 4–hydroxyanisole. From the results, we conclude that the chloroform extract of Cleome chelidonii was found to possess significant Anti-leucoderma activity as compared to the standard drug Psoralen ointment, which produced repigmentation on the 5th day of application, and complete repigmentation occurred in the 4th week in black mice model.